The Balanced scorecard : translating strategy into action - Kaplan, Robert S.; Norton, David P. (Boston, Massachusetts : Harvard Business School Press, 1996)
copy 1 - located at the office of Rhoniel Dimaculangan
Includes index.
Rhoniel Dimaculangan
Keywords: Industrial productivity -- Measurement; Strategic planning; Organizational effectiveness -- Evaluation